Images in clinical medicine: gouty arthritis with osteomyelitis - Rosa Scipioni; Luciano Frate; Valentino Di Tomasso; Michele Saltarelli; Francesco Carubbi; Marco Petrarca (Italian Journal of Medicine, 2018)
Gout is one of the most common inflammatory arthropathies, characterized by the deposition of monosodium urate crystals in the synovial membrane, articular cartilage and periarticular tissues and leading to inflammation. The natural history of articular gout is typically composed of four periods: asymptomatic hyperuricemia, episodes of acute attacks of gout (acute gouty arthritis) with asymptomatic intervals (intercritical gout), and chronic tophaceous gout. Tophi develop in 12-35% of gouty patients without adequate control of uricemia. Initially, they do not cause significant complaints or function limitation of the nearby joints. However, if they become larger, joint instability and movement range limitation, joint function impairment and bone erosions and infection at the sites of their penetration can develop.We report a case of a poorly controlled polyarticular tophaceous gout complicated by osteomyelitis.